ON THE ROLE OF THE “CAUCASIAN TANDEM” IN GUAM - PAPAVA, Vladimer (CENTRAL ASIA AND THE CAUCASUS, 2008)
The disintegration of the U.S.S.R. and collapse of the communist system made significant changes to the geopolitical map of the world. States with similar characteristics rooted in the relatively recent historical past have appeared in the post-Soviet expanse. These states do not have a multitude of state institutions and have inherited the distorted system of the command economy. Since they have no experience in state independence, these countries, in addition to the numerous unresolved domestic tasks, have also found themselves faced with problems caused by the expanding dimensions of globalization.Globalization is characterized today by the creation of regional unions of states with similar interests, thus making it easier for these countries to reach common goals through joint efforts.A variety of different regional unions of the former Soviet republics have formed in the territory of the disintegrated U.S.S.R. And it is interesting that these formations are far from al-ways limited to the post-Soviet expanse. On the contrary, it has become a priority for many of the former Union republics to become members of interstate unions that existed even before the collapse of the Soviet Union, such as NATO and the EU. Whereas this proved a very manageable task for the Baltic states, other countries are still encountering a multitude of obstacles and unresolved issues as they attempt to gain membership in these unions.More than ten years ago, Georgia, Ukraine, Azerbaijan, and Moldova created the regional international organization called GUAM, which is an institutional entity designed to find common interests and coordinate joint action plans. The fact that this structure has existed for many years that each country individually, as well as the organization they represent as a whole still have many unresolved problems. At present, the question of strengthening and devel-oping GUAM is particularly urgent, and it is a priority not only for the states that belong to this structure, but also for the West, the interests of which in the post-Soviet expanse are largely related to the interests of GUAM.GUAM’s development might be successfully promoted by means of the “Caucasian Tan-dem”1 of Azerbaijan and Georgia, which has al-ready largely shown its efficacy and efficiency in resolving many problems that affect the interests of these Caucasian republics.